Integration of Pancasila and Rahmatan Lil 'Alamin Profiles in Madrasah Aliyah Al Iman Ponorogo Curriculum - Wulandari, Sri (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
Education plays a central role in shaping the character and quality of human resources. Quality education does not only focus on knowledge transfer, but also on the formation of students' morals, personalities, and skills. This study discusses the implementation of the Pancasila and Rahmatan Lil 'Alamin student profile strengthening project in Madrasah Aliyah Al Iman Ponorogo, Indonesia. Research shows the success of madrasahs in implementing curriculum principles in accordance with Ministry of Religious Affairs guidelines. However, there are weaknesses in equitable distribution and improvement of the quality of education, especially for Students with Special Needs. Project implementation involves intracurricular and extracurricular activities, focusing on specific subjects. While there have been efforts to shape learners' attitudes, research recommends improvements, including the addition of principles for inclusiveness and educational equity. Involving stakeholders, such as parents and organizations related to GDP, is also considered crucial. Overall, the implementation of the curriculum at MA Al Iman reflects a commitment to the formation of character, religious values, and nationality in accordance with the objectives of national education.